INTERPRETATION OBJECTS OF LAND USE ON SPACE IMAGES IN THE KRASNODAR REGION - Anatoly Valerievich Pogorelov; Dmitry Alexandrovich Lipilin (Вестник Северо-Кавказского федерального университета)
Some results of the identification of various agricultural lands in Krasnodar region are presented. The results were based on Landsat 5 satellite pictures and CORINE European land nomenclature. Appraisal of the land classification was made with using different methods.